Viral vector manufacturing: quality attributes of rAAV used in clinical development - Alcudia, Javier; Wright, John Fraser (Journal of biomolecular techniques, 2020)
Recombinant Adeno-Associated Virus (rAAV) are widely used for human gene therapy, now the basis for two licensed products (for RPE65-/-, and SMA) and numerous other investigational treatments for a range of diseases including hemophilia, cystic fibrosis, muscular dystrophy & many neurological disorders. Process development is complex, time consuming & expensive, with scale-up being a major technology challenge for commercialization. While progress has been made to implement clinical vector production (upstream) and purification (downstream) processes at large scale, required for high dose indications, many challenges remain in vector design, manufacturing methodology & product characterization. Ongoing innovation is required to understand the critical quality attributes of AAV vectors for human use, & to establish suitable and standardized analytical systems to monitor and control clinical manufacturing processes & characterize the purified vector products. ‘Research-grade' vectors are not subject to the same control criteria; however, similar approaches are utilized on a routine basis in cores and research labs to manufacture viral vectors for discovery, investigational product development & IND-supporting studies. In that regard, academic centers should promote and implement good practices and make transferable protocols to accelerate gene therapy drug development. At the GVVC a high-throughput platform has been optimized to produce custom rAAVs with a rapid turnaround and rigorous analytical methods for quality control. These include qualified qPCR titer methodology, purity using a range of tests & functional activity (infectivity) verificdation of the recombinant virus. Furthermore, this core facility borrows from GXP practice for carefully segregated workflow to prevent product cross-contamination in a high throughput environment. the GVVC facility has manufactured over 5000 custom AAV vector batches for Stanford researchers & neuroscientists world-wide.